Effects of Pesticides on Plants - Roshan Satpathy, Rakesh (International Journal of Psychosocial Rehabilitation, 2025)
Pesticides area unit are used to kill the pests and insects that attack on crops and harm them. Totally different varieties of pesticides are used for crop protection for centuries. Pesticides benefit the crops but they conjointly impose a significant negative impact on the setting. Excessive use of pesticides might result in the destruction of biodiversity. Pesticides area unit are priority for sustainability of global and environment stability. Pesticides cause regular harm to established vegetation among the section of agricultural lands. Pesticides promise the effective mitigation of harmful bugs, however sadly, the risks related to their use have surpassed their beneficial effects. Nonselective pesticides kill non-target plants and animals in conjunction with the targeted ones. Moreover, with the passage of time some pests conjointly develop genetic resistance to pesticides